Aligned Metal–Organic Framework Nanoplates in Mixed‐Matrix Membranes for Highly Selective CO2/CH4 Separation. Issue 12 (21st March 2023) - Wang, Lei; Bai, Xianying; Gu, Yawei; Shi, Xinxin; Wang, Shilong; Hua, Jingxian; Hou, Rujing; Wang, Chongqing; Pan, Yichang
Abstract: 2D metal–organic frameworks are attractive filler in mixed matrix membranes (MMMs) due to the high aspect ratio and contact opportunity at the filler–polymer interface. However, their alignment in polymer matrix remains a challenge to fully play their functions. Herein, to our best knowledge, for the first time, the facile synthesis of KAUST‐7‐NH2 (KAUST, King University of Science and Technology) nanoplate is reported with 1D channels with an aspect ratio greater than 30. The nanoplates are incorporated and aligned in the 4, 4′‐(hexafluoroisopropylidene) diphthalic anhydride‐2, 4‐diaminomesitylene (6FDA‐DAM) polymer matrix under the shear force with a filler loading up to 50 wt%. The large difference in adsorption abilities between CO2 and CH4 from the (001)‐oriented KAUST‐7‐NH2 nanoplate‐based MMMs and the favorable interaction at the filler–polymer interface contribute to the excellent CO2 /CH4 separation performance. The resultant membranes show CO2 /CH4 selectivity with 66.2% enhancement (surpassed 2008 Robeson upper bound), antiplasticization up to 17 bar, and long‐term stability up to 240 h indicating its good potential for natural gas treatment. Abstract : KAUST‐7‐NH2 (KAUST, King University of Science and Technology) nanoplates are fabricated with maximally exposed (001) facets and an aspect ratio greater than 30 by a facile ligand doping method for the first time. The nanoplates are aligned in the 4, 4′‐(hexafluoroisopropylidene) diphthalic anhydride‐2, 4‐diaminomesitylene (6FDA‐DAM) polymer by a simple blade coating method to form the highly loaded oriented‐mixed matrix membranes (50 wt% loading) with excellent CO2 /CH4 separation selectivity.